Al Islam Kemuhammadiyahan: Khilafiyah Dan Perbandingan Mazhab - Musdalifah .; Ramlan .; M. Amin (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
Diversity of opinion (khilafiyah) and schools of Islamic legal thought (mazhab) are inseparable phenomena in the history of Islamic development. This research focuses on examining the basic concept of khilafiyah and the existence of mazhab within the framework of Al-Islam KeMuhammadiyahan. This study uses a qualitative method of library research, examining classical fiqh literature, the history of Islamic law, and the Muhammadiyah Tarjih guidelines. The discussion focuses on two main points: First, the nature of madhhab as a systematic methodology (manhaj) in exploring law, not merely the opinions of prominent figures. Second, the nature of khilafiyah as a logical consequence of differences in methodology in the realm of furu'iyah (branches of religion), not in the realm of ushul (principles of faith). The results of the study indicate that the dynamics of khilafiyah arise due to variations in the understanding of the text of the dalil and differences in sociological conditions between madhhabs. From a Muhammadiyah perspective, a complete understanding of the position of madhhab and the causes of khilafiyah is very important to avoid blind fanaticism (taqlid) and build a moderate (wasathiyah) and tolerant religious attitude amidst differences in the community.